Revitalizing Senior High School Streaming Through Adaptive Assessment and Career Services - Syafryanto Adam; Ribut Wahyu Eriyanti; Muhamad Supian (International Journal of Education, Management, and Technology, 2026)
Flexible curriculum policies have been widely adopted to promote student autonomy and personalized learning in secondary education, yet in practice academic streaming within these systems often encounters substantial challenges, including limited student readiness, fragmented career guidance, and inconsistent school-level implementation. These conditions can produce pseudo-flexibility, whereby students’ subject choices are constrained more by institutional capacity than by their interests and abilities. This study aims to analyze the challenges of senior high school academic streaming in flexible curriculum contexts and to develop a conceptual model that revitalizes streaming through the integration of adaptive assessment and career services. Using a qualitative research design, the study employs policy analysis and a systematic literature review of national education policies, peer-reviewed journal articles, and international reports related to curriculum management, assessment, and career guidance. The findings indicate that effective academic streaming requires three interrelated components: adaptive assessment to generate data-informed student profiles, structured career services to provide continuous guidance and decision support, and interdisciplinary learning pathways to operationalize curricular flexibility in a coherent and meaningful manner. The proposed model positions academic streaming as a managed, student-centered process that aligns pedagogical practices with educational management and educational technology. The study contributes theoretically by offering an integrative framework that bridges gaps between assessment, career guidance, and flexible curriculum policy, and practically by providing a strategic reference for policymakers and school leaders. Future research is recommended to empirically test the proposed model in school settings to evaluate its impact on academic alignment, career readiness, and educational equity.